Effect of Fertilizers on the Yield of Alternative Small Grains - Dolijanović Željko; Kovačević Dušan; Oljača Snežana; Roljević Nikolić Svetlana; Šeremešić Srđan (Contemporary Agriculture, 2017)
The purpose of this study is to evaluate the effect of organic farming technologies on the yield of alternative types of wheat: hard wheat (Triticum durum), spelt (Triticum aestivum ssp. spelta) and a common variety of (soft) winter wheat (Triticum aestivum ssp. vulgare). The experiment was carried out during 2010-11 and 2011-12, at the Radmilovac experimental field of the Faculty of Agriculture in Belgrade, according to the randomized block design in four replications. In addition to the control treatment (without fertilizers), microbiological fertilizers were applied in topdressing (alone) and in combination with organic fertilizer before sowing. Crops were grown under a four-crop rotation on leached chernozem in the rainfed water regime. The average yields of the varieties examined were not significantly different depending on the growing year, whereas fertilization showed a highly significant effect on the grain yield. The combined application of microbiological and organic fertilizers resulted in the highest yields in both years (5,209 and 4,992 kg ha-1, respectively). The selected wheat varieties exhibited different responses to the treatments applied. The highest yield was observed in the common soft wheat variety examined (5,170 and 5,611 kg ha-1), whereas the lowest in durum wheat (3,138 and 2,429 kg ha-1). The analysis of experimental factor interactions showed that statistically significant effects on the yield could be attributed to the year-fertilization interaction. The wheat yields obtained are similar to those observed in the conventional production system due to favorable weather conditions and a proper selection of the type and sequence of crops that are part of the four-crop rotation (winter wheat, maize, spring barley + red clover, and red clover).